Integral-Type Operators from Bloch-Type Spaces to QK Spaces - Stevo Stević; Ajay K. Sharma (Abstract and Applied Analysis)
The boundedness and compactness of the integral-type operator Iφ,g(n)f(z)=∫0zf(n)(φ(ζ))g(ζ)dζ, where n∈N0, φ is a holomorphic self-map of the unit disk D, and g is a holomorphic function on D, from α-Bloch spaces to QK spaces are characterized.